A Review Study on the Main Sources of Porosity in Al-Si Cast Alloys. (22nd June 2021) - Samuel, Agnes; Zedan, Yasser; Doty, Herbert; Songmene, Victor; Samuel, Fawzy. H.
Abstract : The present study was performed on A356 and B319 alloys in mechanically stirred or degassed condition. Melts were Sr-modified and grain-refined. Hydrogen content was varied from less than 0.1 ml/100 g Al to ∼0.4 ml/100 g Al; Fe was increased to 0.8% in B319 alloy. Lanthanum and cerium were added as 99.5% pure metals. Two main techniques were used to investigate porosity formation: fracture surface of tensile or fatigue test bars, or reduced pressure test (RPT) method. Porosity type and shape were examined. The results show that pore size is more influential than small scattered ones from a mechanical point of view. Tensile testing is affected by porosity located at the center of the testing bar, whereas edge porosity is responsible for crack initiation in case of fatigue testing. Intermetallics precipitate in the form of intercepted platelets which restricts the flow of the molten metal, leading to formation of shrinkage cavities. Precipitation of clusters of compounds from the liquid state such as Al2 Si2 Sr, Mg2 Sn, Al3 Ti, or added Al2 O3 particles would as well act as nucleation sites for porosity formation. Most oxides were observed in the form of long branched strings. In some cases, bifilms were also reported in addition to SrO and MgO.